Accommodating project-based professionals in higher education institutions in Japan. Issue 3 (4th May 2018) - Takagi, Kohei
ABSTRACT: In the shifting environment of higher education, characterised by financial constraints, institutional competition and governmental steering, universities adopt a new stream of missions. In Japan, internationalisation and the acquisition of a global outlook have become a key strategy. The trend is endorsed through competitive public funding schemes, based on the belief that competition fosters so-called world-class universities. These schemes necessitate not only internationalisation of curriculum and research but also a wide range of projects and programs, which require talents that may not be readily found in the existing cadres of university workers. This empirical research assesses experiences and perceptions of project-based professionals in Japanese universities. It found unique ways in which 'Specially appointed academic staff' are given project and administrative responsibilities but with limited access to environment and/or support system for research. Discussions focus on impacts of such appointment on their academic career and explore how these institutional projects may be handled in regards to university organisation.